Study on The Use of Genjer Plant (Limnocharis flava) as Adsorbent of Copper (Cu2+), Lead (Pb2+), and Zinc (Zn2+) Metal Ion in Water - Chairuddin (Talenta Publisher, 2020)
The use of Genjer (Limnocharis flava) as an adsorbent for ions of Copper (Cu2+), Lead (Pb2+), and Zinc (Zn2+) contents in the water has been studied. Firstly, Genjer powder was cut to pieces, dried, blended, and activated with HCl 10% for 24 hours. The two grams powder of Genjer was activated by HCl 10% added into each 100 mL copper (Cu2+) standard solution, lead (Pb2+) standard solution, and zinc (Zn2+) standard solution with a concentration 20 mg/L. Stirred for 24 hours, filtered and measured concentrations ions of copper (Cu2+), lead (Pb2+), and zinc (Zn2+) using an Atomic Absorption Spectrophotometer (AAS). The result of the research showed that the powder of Genjer (Limnocharis flava) that has been activated by HCl 10% can absorb copper (Cu2+) 96.083%; lead (Pb2+) 99.33% and zinc (Zn2+) 96.28%.